Effect of the Cooperative Learning Model Type STAD for Nyurat Lontar Skill of Students - I Gede Rivandi Prasetya; Komang Puteri Yadnya Diari; Made Reland Udayana Tangkas (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
The primary goal of education is to develop the skills of each student. These skills will be invaluable in the future. One skill essential for preserving Balinese culture is writing on palm leaves, also known as nyurat lontar. Nyurat lontar is practiced in schools. Encouraging this requires various aspects, one of which is the learning model. This study was conducted to determine the effect of the Cooperative Learning model type STAD on the writing skills of class X students in SMA Negeri 1 Pupuan. This study selected a population of class X, comprising a total of 267 students, and took a sample of class X6 as the control class and class X8 as the experimental class. This study employs a quantitative research approach with a quasi-experimental design, specifically a nonequivalent control group design. The selected experimental class group will receive treatment, while the control class will not. The final value will be compared to determine whether the treatment given by the researcher has an effect on the Cooperative Learning model type STAD's impact on the skills of Nyurat Lontar in that class. Based on the posttest results, it is known that the hypothesis test of the Independent Samples Test of Lontar Writing skills obtained a significance (2-tailed) of 0.000. The basis of decision-making is that if p-value (2-tailed) < 0.05, then Ha is accepted and H0 is rejected. This indicates that Ha is accepted, which suggests that the Cooperative Learning model type STAD has an impact on the long-term writing skills of class X students at SMA Negeri 1 Pupuan. With the STAD type of cooperative learning model, the practical activity of nyurat lontar becomes easier to implement, and this activity can be useful for preserving culture so that it does not disappear alongside the development of the times.